Positive Solutions for (n-1,1)-Type Singular Fractional Differential System with Coupled Integral Boundary Conditions - Ying Wang; Lishan Liu; Xinguang Zhang; Yonghong Wu (Abstract and Applied Analysis)
We study the positive solutions of the (n-1,1)-type fractional differential system with coupled integral boundary conditions. The conditions for the existence of positive solutions to the system are established. In addition, we derive explicit formulae for the estimation of the positive solutions and obtain the unique positive solution when certain additional conditions hold. An example is then given to demonstrate the validity of our main results.